Correlation between Insulin Resistance and Thyroid Nodule in Type 2 Diabetes Mellitus - Yunzhao Tang; Tiantian Yan; Gang Wang; Yijun Chen; Yanjuan Zhu; Zhenhuan Jiang; Min Yang; Chenguang Li; Zhu Li; Ping Yu; Shanshan Wang; Nannan Zhu; et al. (International Journal of Endocrinology)
Objective. The present study explored the association between insulin resistance (IR) and the clinical characteristics of thyroid nodules in patients with type 2 diabetes mellitus (T2DM). Methods. All the patients were newly diagnosed with T2DM. 201 patients with thyroid nodule disease and 308 patients without the nodular thyroid disease. The participants were evaluated by relevant examination. Correlation analyses and regression analyses were performed to examine the relationships between the two groups. Results. HOMA-IR values, serum FT4 (free thyroxine) levels, and age were higher in the thyroid nodule group than in the control group. The proportion of women in the thyroid nodule group is greater than the proportion of women in the control group. Logistic regression analysis showed that age, sex, FT4, and HOMA-IR were positive factors for thyroid nodule. The volume and size of the thyroid nodule were positively correlated with HOMA-IR, irrespective of gender. The thyroid nodule volume and size and the TSH (thyroid stimulating hormone) were greater in females than in males, whereas FT3 (free triiodothyronine) was lower in females. Conclusion. IR might be a risk factor for thyroid nodule. Whether alleviating the IR might slow the growth, or diminish the volume and size of the thyroid nodules, is yet to be elucidated.